Recent Progress on the Dispersion and the Strengthening Effect of Carbon Nanotubes and Graphene-Reinforced Metal Nanocomposites: A Review - Baig, Z. (Taylor and Francis Inc., 2018)
This article reviews the available literature published to date on the reinforcement of metals with carbon-nanofillers (CNTs and graphene), and also offers a specific focus on issues related to the mechanical and tribological properties of nanocomposites. Carbon-nanofillers (later denoted by C-nanofillers) are known to have extraordinary mechanical properties and multifaceted characteristics and are ideal candidates for the reinforcement of metals for numerous applications. However, their incorporation for practical applications has been challenging researchers for decades. The most important issue is uniform dispersion due to sizeable surface differences between carbon-nanofillers and metals. Other concerns are structural integrity, wetting with metals, and interfacial connections. Nanocomposite applications can only be effective when these challenges are properly addressed and overcome. Section 1 assesses the importance of C-nanofillers and expressly highlights current research efforts to optimize dispersion in different metals along with processing techniques in section 2. The authors give special attention on C-nanofillers reinforcement contribution to enhanced mechanical strength of metals presented in section 3. C-nanofillers dispersion evaluation tools are highlighted in section 4. Authors also focuses on C-nanofillers role and factors directly associated with metal nanocomposite strength, as reported in the literature. Particular consideration is also given to knowledge sharing of attendant strengthening mechanisms along with contribution reported for empirically derived models used to predict strength. Section 6 solely dedicated to the tribological aspects of C-nanofillers reinforced metallic nanocomposites. Lastly, future recommendations and works need attention is summarized. Â© 2018 Taylor & Francis Group, LLC.